Enhancing Employee Performance with E-Training and Work Environment through Work Motivation - Rochmah Candra Dewi; Ika Nurul Qamari; Sri Handari Wahyuningsih; Mohsin Shaikh (Relevance: Journal of Management and Business, 2023)
Employee performance studies are becoming more common as new behaviors emerge in Industry 4.0. The purpose of this study is to investigate how E-Training and the Work Environment influence Employee Performance, with Work Motivation acting as a mediator. The research was carried out in the banking industry in Yogyakarta, Indonesia. The data collection approach employs a survey method, with questionnaires distributed to bank staff. Data was acquired using a simple random sampling technique. Using the Smart PLS 4.0 computer application, data analysis was performed to test the given hypothesis. The research results show that just two of the five hypotheses given are supported, namely that the work environment has a substantial effect on work motivation and employee performance. Meanwhile, work motivation has no effect on employee performance, e-training has no effect on work motivation and employee performance. The discussion of the findings is explained in this article